Seizures as a clinical manifestation in somatic autoimmune disorders. (January 2019) - Amanat, Man; Thijs, Roland D.; Salehi, Mona; Sander, Josemir W.
Highlights: Autoimmune disorders are often co-morbid with epilepsy. Risk of epilepsy may be increased in autoimmune conditions. Shared risk factors may contribute to the comorbidity. Immune dysfunction may play a role in the genesis of seizures. Elevated levels of cytokines and auto-antibodies may decrease seizure threshold. Abstract: The risk of epileptic seizures seems increased in several systemic autoimmune disorders including systemic lupus erythematosus, type 1 diabetes mellitus, myasthenia gravis, celiac disease, rheumatoid arthritis, Hashimoto's encephalopathy, psoriasis, multiple sclerosis, neuromyelitis optica, and bullous pemphigoid. Immune dysfunction may be partly responsible for this association. Elevated levels of pro-inflammatory cytokines, autoantibodies seen in these autoimmune disorders and antibodies against neuronal antigens may contribute to the etiopathogenesis of seizures and epilepsy associated to immune conditions. Other unknown factors, the effect of different co-morbid conditions of epilepsy as well as shared risk factors such as common etiological factors, environmental triggers, or a common genetic predisposition may also explain the association. We review different autoimmune disorders which may present with co-morbid seizures and discuss possible underlying mechanisms of this co-occurrence focusing on a potential role of immune system dysfunction.